Distillers Grain Prices: Spatial Relationships, Arbitrage Opportunities & Risk Management - Schroeder, Ted C. (North American Institute for Beef Economic Research; Kansas State University Agricultural Experiment Station and Cooperative Extension Service, 2010)
Distillers grain (DG) production in the US has increased from less than 5 million metric tons at the start of the decade to more than 20 million metric tons in 2008. This rapidly expanding market has increased the need to better understand price relationships, determine how price discovery occurs, and to assess price risk management alternatives. This fact sheet was completed to address these specific issues.